2018
DOI: 10.1016/j.cell.2017.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Induction of Trained Immunity through the Mevalonate Pathway

Abstract: Innate immune cells can develop long-term memory after stimulation by microbial products during infections or vaccinations. Here, we report that metabolic signals can induce trained immunity. Pharmacological and genetic experiments reveal that activation of the cholesterol synthesis pathway, but not the synthesis of cholesterol itself, is essential for training of myeloid cells. Rather, the metabolite mevalonate is the mediator of training via activation of IGF1-R and mTOR and subsequent histone modifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
528
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 567 publications
(588 citation statements)
references
References 57 publications
24
528
0
3
Order By: Relevance
“…Additionally, cholesterol overload in hematopoietic progenitors could also lead to a sustained state of intracellular stress, linked to increased inflammatory signaling and a potential long-term reprogramming. Supportively, the studies by Bekkering et al (2018 [this issue of Cell ]) reported in this issue of Cell show that dysbalanced cholesterol biosynthesis with an accumulation of mevalonate can drive trained immunity induction. On the other hand, it appears plausible that NLRP3 could also instigate inflammatory pathologies toward a range of sterile danger signals not limited to WD, as numerous triggers of relevance in human chronic inflammatory pathologies have been linked to NLRP3 activation (Heneka et al, 2013; Hornung et al, 2008; Martinon et al, 2006).…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, cholesterol overload in hematopoietic progenitors could also lead to a sustained state of intracellular stress, linked to increased inflammatory signaling and a potential long-term reprogramming. Supportively, the studies by Bekkering et al (2018 [this issue of Cell ]) reported in this issue of Cell show that dysbalanced cholesterol biosynthesis with an accumulation of mevalonate can drive trained immunity induction. On the other hand, it appears plausible that NLRP3 could also instigate inflammatory pathologies toward a range of sterile danger signals not limited to WD, as numerous triggers of relevance in human chronic inflammatory pathologies have been linked to NLRP3 activation (Heneka et al, 2013; Hornung et al, 2008; Martinon et al, 2006).…”
Section: Discussionmentioning
confidence: 76%
“…Glutaminolysis represents another metabolic reconfiguration observed in immune training of cells with β‐glucan, and inhibition of this metabolic shift leads to reduced induction of trained immunity in vivo . Similarly altered immune states with enhanced inflammatory cytokine production associated with epigenetic modifications have not only been observed in settings using microbial stimulations, but also in response to sterile ligands such as oxLDL or hypercholesterolemia in the context of atherosclerosis …”
Section: The Innate Immune System and Innate Immune Memorymentioning
confidence: 99%
“…An important novel observation is that statins also impact the immune system through effects on immune cell metabolism. Recently a study showed that activation of the cholesterol synthesis pathway was essential for immunological training of myeloid immune cells . The study also reported that the metabolite mevalonate is the mediator of training through activation of insulin‐like growth factor 1 receptor and mammalian target of rapamycin and subsequent histone modifications in inflammatory pathways .…”
Section: Mechanisms Of Actions Of Statins On Different Immune Cellsmentioning
confidence: 99%